Revisiting the factors influencing corporate dividend policy decisions: evidence from listed banks in Ghana / Ibrahim Nandom Yakubu - Yakubu, Ibrahim Nandom (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2019)
Dividend policy determinants have been explored for decades, yet a consensus on the factors that determine dividend policies among firms has not been so far established as findings differ depending on the industry and sector. This paper aims to contribute to the existing literature by examining the factors influencing dividend policy of listed banks in Ghana relying on bank-level data spanning 2006 – 2015. Using the pooled ordinary least squares, fixed and random effects as estimation techniques, the findings show that dividend policy of banks is significantly driven by bank growth, profitability, bank size, and leverage. Capital adequacy ratio and domestic macroeconomic instability proxied by inflation were found to be insignificant. The findings lend strong support for the agency cost theory and the pecking order hypothesis of dividend policy.